Music, scholasticism and reform Salian Germany, 1024 - 1125 - McCarthy, Thomas John Henry (Manchester medieval studies, 2009)
Making German scholarship available in English, this book deals with music as an intellectual discipline. It introduces the south-German circle, discusses dialectic and the theory of music, explores the influence of Plato, and looks at the music theory manuscripts of the 11th and 12th centuries.